2019
DOI: 10.1101/523712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transposable elements drive reorganisation of 3D chromatin during early embryogenesis

Abstract: Transposable elements are abundant genetic components of eukaryotic genomes with important regulatory features affecting transcription, splicing, and recombination, among others. Here we demonstrate that the Murine Endogenous Retroviral Element (MuERV-L/MERVL) family of transposable elements drives the 3D reorganisation of the genome in the early mouse embryo. By generating Hi-C data in 2-cell-like cells, we show that MERLV elements promote the formation of insulating domain boundaries throughout the genome in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 68 publications
3
56
1
Order By: Relevance
“…It is intriguing to speculate, whether activation of ERVL-MaLR elements together with the DUX4 enhancerome provides a correct ‘genomic niche’ for the subsequent genome activation step. It was recently shown that in mouse Dux binding at Mervl loci drives chromatin reorganisation at these loci in 2-cell embryo-like cell lines, and that chromatin organisation during early mouse development is a consequence of the Mervl integration 41 . To date, human 2-cell-like cell lines have not been established, but importantly, in our experiments, activation of the DUX4 and its likely binding at ERVL-MaLR elements 6 could modify chromatin towards human cleavage embryo-like stage in the hESCs.…”
Section: Discussionmentioning
confidence: 99%
“…It is intriguing to speculate, whether activation of ERVL-MaLR elements together with the DUX4 enhancerome provides a correct ‘genomic niche’ for the subsequent genome activation step. It was recently shown that in mouse Dux binding at Mervl loci drives chromatin reorganisation at these loci in 2-cell embryo-like cell lines, and that chromatin organisation during early mouse development is a consequence of the Mervl integration 41 . To date, human 2-cell-like cell lines have not been established, but importantly, in our experiments, activation of the DUX4 and its likely binding at ERVL-MaLR elements 6 could modify chromatin towards human cleavage embryo-like stage in the hESCs.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are only a few genomic loci for which HDAC inhibition or DNA methylation loss appears to be directly responsible for altered TF binding and transcriptional activity, these elements are of biological and potentially clinical significance. LINEs and ERVLs for example, are reported to be essential for early embryonic development following fertilisation (Jachowicz et al, 2017;Kruse et al, 2019;Percharde et al, 2018), a period during which histone acetylation is elevated and DNA methylation is low (Eckersley-Maslin et al, 2016;Ishiuchi et al, 2015;Macfarlan et al, 2012). In somatic tissues, aberrant expression of germ-cell specific genes and retrotransposons is likely to be detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…The ERVL LTR promoter drives early cleavage‐stage specific genes in both mouse and human embryos, and has been associated with zygotic/embryonic genome activation . Most recently, both MERVL and HERVH elements have been implicated in 3D genome organization, where their presence can affect TAD boundaries as well as nearby gene expression . As genome‐wide mapping and analysis tools continue to improve, it is likely that many more examples of TE‐derived cis ‐regulatory elements and networks will be uncovered.…”
Section: Te Dna and The Evolution Of Cis‐regulatory Networkmentioning
confidence: 99%